2017
DOI: 10.1002/hep.29217
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐onset cystic fibrosis liver disease: Diagnosis and characterization of an underappreciated entity

Abstract: Background & Aims Cystic fibrosis liver disease (CFLD), a leading cause of death in cystic fibrosis (CF), is mostly described in pediatric populations. Adult-onset CFLD lacks sufficient characterization and diagnostic tools. Methods A cohort of CF patients without CFLD during childhood were followed for up to 38 years with serologic testing, imaging, and noninvasive fibrosis markers. Historical CFLD diagnostic criteria were compared with a newly proposed CFLD criteria. Results 36 CF patients were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 45 publications
7
107
1
Order By: Relevance
“…Furthermore, in these two studies, patients were only followed up over a short time, meaning that limited information was available to estimate CFLD incidence over the patients’ lifetime. In accordance with our findings, a recent study reported that adult‐onset CFLD was likely underestimated . The improved survival of patients with CF in the last decade may also explain the change in the incidence profiles of CFLD…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, in these two studies, patients were only followed up over a short time, meaning that limited information was available to estimate CFLD incidence over the patients’ lifetime. In accordance with our findings, a recent study reported that adult‐onset CFLD was likely underestimated . The improved survival of patients with CF in the last decade may also explain the change in the incidence profiles of CFLD…”
Section: Discussionsupporting
confidence: 73%
“…In general, CFLD is felt to be an emerging entity, Koh C. et al recently emphasized [39] the lack of sufficient characterisation and diagnostic tools for the diagnosis of adult-onset CFLD. They found that only 22% of CF patients had CFLD, based upon the Debray criteria, which they felt was likely an underestimation of actual disease.…”
Section: Discussionmentioning
confidence: 99%
“…Factors independently associated with liver disease have included a history of meconium ileus, pancreatic insufficiency, colonization with Burkholderia cepacia , and the number of episodes per year requiring intravenous (IV) antibiotic therapy . Although early studies suggested that the majority of these cases are in pediatric patients, recent studies suggest that liver disease may be more common in adults with CF than previously predicted . This may be related to newer modalities for assessment of liver disease not previously available.…”
Section: Cf‐associated Liver Diseasementioning
confidence: 99%
“…At the time of the initial consensus criteria proposed by Debray et al in 2011, there was insufficient validation to support the use of noninvasive methods of assessment of fibrosis, such as transient elastography, or to incorporate them into the definition of CFLD. More recent publications have proposed the inclusion of these fibrosis assessments and reliance on radiographic evidence of cirrhosis or diffuse liver disease, rather than on physical examination …”
Section: Diagnosis Management and Treatment Of Liver Disease In Cfmentioning
confidence: 99%